Urban services delivery in Limbo: a provisional assessment of Gweru’s water supply system - Matsa, Mark (David Publishing, 2014)
This study sought to assess Gweru’s water supply system from the source to the consumer to find out whether the water is safe for domestic purposes, mainly consumption. Water samples were taken from Gwenoro dam (raw water), Gwenoro treatment plant (treated water) as well as from GIS-generated random points of residential areas closest to Gwenoro and furthest from both the dam and the treatment plant. These were taken for laboratory testing where parameters like pH, hardness, turbidity and DO (dissolved oxygen) were tested. Questionnaires were used to solicit the views of the consumers on water quality and water service delivery from eight randomly selected residential suburbs. Interviews were also administered to Gwenoro Water Treatment Plant superintendent and deputy to get insight into the day to day challenges that they have to grapple with. Results generally show that treated water from Gwenoro treatment plant is relatively safe to drink for those who have access to it. However, some consumer points like Mkoba 13 and Mkoba 18 receive water whose DO is out of the recommended range. Suburbs which lie on higher ground like Mkoba 19 and Mkoba 14 however rarely receive water from Gwenoro with some residents of Mkoba 19 having had no water from their taps for more than three years now. The study recommends that new equipment be bought for the treatment plant so that treated water reaches all parts of the city. Newly resettled farmers in the Upper Runde Catchment must be resettled elsewhere while urban stream bank cultivation must be banned to reduce water pollution as well as possible sedimentation of Gwenoro dam.